2018
DOI: 10.3847/1538-3881/aab8ff
|View full text |Cite
|
Sign up to set email alerts
|

OSSOS. VIII. The Transition between Two Size Distribution Slopes in the Scattering Disk

Abstract: The scattering trans-Neptunian Objects (TNOs) can be measured to smaller sizes than any other distant small-body population. We use the largest sample yet obtained, 68 discoveries, primarily by the Outer Solar System Origins Survey (OSSOS), to constrain the slope of its luminosity distribution, with sensitivity to much fainter absolute H-magnitudes than previous work. Using the analysis technique in Shankman et al., we confirm that a single slope for the H-distribution is not an accurate representation of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
133
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(140 citation statements)
references
References 59 publications
6
133
1
Order By: Relevance
“…Our initial conditions for the simulations consist of 8500 TNO particles; only particles whose semimajor axes changed by 1.5au or more within the last 10Myr of the Kaib et al (2011) model run are included, as this is how the observed actively scattering TNO population is defined. Shankman et al (2016) and Lawler et al (2018) found that these initial conditions provide an adequate representation of the population of scattering TNOs observed by the Canada France Ecliptic Plane Survey (CFEPS; Petit et al 2011), the Outer Solar System Origins Survey (OSSOS; Bannister et al 2016bBannister et al , 2018, and Alexandersen et al (2016). We numerically integrate the orbits of the model scattering population as massless test particles using the rmvs3 routine in SWIFT (Levison & Duncan 1994) with the Sun and the four giant planets included as massive bodies.…”
Section: Initial Conditions: a Model Of The Current Scattering Populamentioning
confidence: 99%
See 4 more Smart Citations
“…Our initial conditions for the simulations consist of 8500 TNO particles; only particles whose semimajor axes changed by 1.5au or more within the last 10Myr of the Kaib et al (2011) model run are included, as this is how the observed actively scattering TNO population is defined. Shankman et al (2016) and Lawler et al (2018) found that these initial conditions provide an adequate representation of the population of scattering TNOs observed by the Canada France Ecliptic Plane Survey (CFEPS; Petit et al 2011), the Outer Solar System Origins Survey (OSSOS; Bannister et al 2016bBannister et al , 2018, and Alexandersen et al (2016). We numerically integrate the orbits of the model scattering population as massless test particles using the rmvs3 routine in SWIFT (Levison & Duncan 1994) with the Sun and the four giant planets included as massive bodies.…”
Section: Initial Conditions: a Model Of The Current Scattering Populamentioning
confidence: 99%
“…To generate these predictions, we use the constraints on the scattering population from OSSOS (Bannister et al 2016b(Bannister et al , 2018. Based on the number of scattering objects detected in this survey, Lawler et al (2018) estimated that there are 1.1± 0.2×10 4 scattering objects with H r <8.66 and semimajor axes in the range 30-100 au. Producing this estimate relies on assuming a model for the true orbital and H-magnitude distribution of the scattering population.…”
Section: Predictions For the Transient Resonance Populationsmentioning
confidence: 99%
See 3 more Smart Citations